2006
DOI: 10.1111/j.1365-2710.2006.00708.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of claritromycin on inflammatory parameters and clinical conditions in children with bronchiectasis1

Abstract: Use of CAM in children with steady-state bronchiectasis results in laboratory improvement by reducing the inflammatory processes in the lungs. No corresponding clinical improvement could be shown but although this is possible with long-term use, trial validation is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 22 publications
2
69
0
4
Order By: Relevance
“…Although the comparison of the outcomes of these studies is limited by the different treatment regimens, doses, drug formulations and clinical factors evaluated, low-dose CLM seems to be more effective, as supported also by its low-dose benefits in the treatment of diffuse panbronchiolitis which shares many similarities in clinical and pathological characteristics with CF [1923]. Moreover, CLM treatment was shown to decrease lung inflammatory processes and chronic airways hypersecretion in non-CF patients with bronchiectasis [24,25]. Pertaining to its anti-pseudomonal effects, CLM has no bactericidal activity against P. aeruginosa , like other macrolides, but can interfere with protein synthesis and inhibit protease expression, twitching motility and biofilm maturation, promoting biofilm permeability and favoring penetration of other antimicrobial agents like ciprofloxacin and tobramycin, also used in CF therapy [2628].…”
Section: Introductionmentioning
confidence: 99%
“…Although the comparison of the outcomes of these studies is limited by the different treatment regimens, doses, drug formulations and clinical factors evaluated, low-dose CLM seems to be more effective, as supported also by its low-dose benefits in the treatment of diffuse panbronchiolitis which shares many similarities in clinical and pathological characteristics with CF [1923]. Moreover, CLM treatment was shown to decrease lung inflammatory processes and chronic airways hypersecretion in non-CF patients with bronchiectasis [24,25]. Pertaining to its anti-pseudomonal effects, CLM has no bactericidal activity against P. aeruginosa , like other macrolides, but can interfere with protein synthesis and inhibit protease expression, twitching motility and biofilm maturation, promoting biofilm permeability and favoring penetration of other antimicrobial agents like ciprofloxacin and tobramycin, also used in CF therapy [2628].…”
Section: Introductionmentioning
confidence: 99%
“…A placebo-controlled trial of children with bronchiectasis treated with clarithromycin for 3 months showed no change in FEV1, although maximal mid-expiratory flow (FEF25-75) was significantly improved and there was a significant reduction in sputum volume [33]. A reduction in bronchoalveolar lavage (BAL) fluid IL-8 concentration was seen in the treatment arm, but no change in pathogens or other measures of inflammation, including IL-10 and tumour necrosis factor-a, was measured.…”
Section: Bronchiectasismentioning
confidence: 99%
“…According to the vicious cycle hypothesis, if infection is the primary driver of airway inflammation, bacterial clearance through the use of short-or long-term antibiotic therapy would be expected to reduce airway inflammation, allow airway healing and modify the long-term course of the disease. Until very recently, the role of macrolide therapy in non-CF bronchiectasis had only been investigated in studies that were small, of short duration and did not assess clinical relevant outcomes, such as pulmonary exacerbations and quality of life [44][45][46][47]. In a recently published, randomised, double-blind, placebo-controlled trial, 141 patients (aged o18 years) with a diagnosis of bronchiectasis as defined by HRCT and at least one pulmonary exacerbation requiring antibiotic treatment in the previous year, were assigned to receive azithromycin 500 mg three times per week or placebo for 6 months in a 1:1 ratio [48].…”
Section: Non-cf Bronchiectasismentioning
confidence: 99%